Preface to the health-psychology article collection - Anagnostopoulos, Fotios (Psychology: the Journal of the Hellenic Psychological Society, 2024)
Health psychology is a relatively new subfield of psychology that emphasizes the biopsychosocial model, where physical well-being and disease reflect a complex set of interrelated processes, involving psychological, social, and biological factors. Health psychologists use psychological science to promote health, prevent illness, and improve health care systems. Despite significant advancements in research and practice, the field faces numerous challenges, such as the application of technology and telehealth to monitoring health behaviors, the integration of mental health care with physical health services, the reduction in health disparities, the shift towards primary and secondary prevention, the adoption of an interdisciplinary collaboration approach, and the development and implementation of policy and advocacy strategies. In this special issue, six health psychology-related papers are included that address the role of coping and stress mindset in the intensity of stress responses, the importance of emotional states and expert influence in vaccination decisions against human papillomavirus, the posttraumatic growth of community residents and healthcare workers during the COVID-19 pandemic, the impact of COVID-19 fear on healthcare professionals’ quality of life, the relationship between COVID-related stress and COVID-related immunity and self-regulation factors, as well as the associations between optimism and health orientation during the COVID-19 pandemic. By examining psychosocial factors related to health problems and health-related issues, the authors have contributed to advancing our understanding of how such factors can help individuals better manage and cope with health challenges. The findings from these studies may help inform targeted interventions and strategies to improve overall well-being and address the psychological aspects of health and illness, particularly in the context of global health problems.